Analysis of Film-Based Recitation Learning Using a Social Construction Approach to Southeast Asia History Learning - Soeharso, R; Lestari, Puji; Prasetyo, Kuncoro Bayu; Rosari, Arnia Fenti (Universitas Negeri Semarang, 2024)
History lessons that focus on developing alternative teaching materials and film-based recitation learning models that foster students' interest in learning history are rarely applied in the realm of learning. Even though this process can stimulate the development of students' sense of nationalism through contextual learning. The research questions posed are 1) how to use the film-based recitation learning model in the history of Southeast Asian conflicts; 2) How is the history teacher's social construction regarding film-based recitation learning models on the history of conflict in Southeast Asia? This study contributes to knowing history teachers' thinking constructs about film-based recitation learning models and their effectiveness in learning. This research was conducted using a basic research method with a case study research approach and adopted by researchers looking at cases, selected as objects that are unique, linked to the background of the case, which has a special context with social, cultural, economic, political aspects, as well as in the implementation of the research found very qualified informants who were qualified, then a case analysis unit was carried out. The final stages of the research will also be closed with a focus discussion to evaluate the course of the research and the social construction of history teachers. The study concluded that learning Modern Southeast Asian History with the film media recitation model can improve student learning outcomes in learning history at the senior high school level.